On the History of the Formation of Assyrian Diasporas in Cities on the Riga Railway - Sergei S. Mikhailov (Publishing house "Sreda", 2021)
In the article the author talks about a local episode in the history of the formation of one of the little-studied diasporas of the cities of Central Russia - the Assyrians. The author's goal is to consider the emergence of communities of the considered ethnic group using the example of small Assyrian diasporas known from the Riga Railway. Since the Assyrians settled in the cities of European Russia for the most part after exodus from their places of traditional residence, fleeing the genocide unleashed by the Turkish authorities during the First World War, their new places of residence anyway were tied to the lines of the railways that existed at that time. For this study, the Riga (formerly Vindava) direction was chosen, about the Assyrians of which the author has so far collected the maximum possible information. Based on the materials of the largest researcher of the Assyrian diaspora of the former USSR - archimandrite Stephen (Sado), as well as on the materials of his own field research, the author provides the reader with information on the diasporas that arose at the early stage of the formation of the Russian Assyrian community - in the 1920s-1930s. The article deals with the Assyrians of the former city of Tushino, which in 1960 became part of Moscow, Istra, Volokolamsk, Rzhev, Velikiye Luki, Toropets, located on the territory of the Moscow, Tver and Pskov regions of the Russian Federation. First of all, the participation of families from different tribal and rural communities in the formation of diasporas is considered, as a result, the author identifies at least three parts on this railway direction, inhabited by people from certain tribes. The first part, which includes the former city of Tushino and, possibly, Istra and Volokolamsk, is represented by the diasporas of the Jylu tribe. In the second, on the indicated railway direction, we include only the city of Rzhev. There, first of all, we see two groups of families of people from the village. Kochanis (Kuchisnaya tribe) and the Diz region (Diznaya). The latter point allows us to consider the city as part of the settlement area of the diasporas of this group, which includes some cities of the Tver and Smolensk regions, located along the adjacent Torzhok - Vyazma branch. The third part is the cities of Velikiye Luki and Toropets, in which we know mainly the Assyrians of the Shapatna group, who in the 1920-1930s created a large array of settlement of their diasporas, covering part of the north-west of Russia, Belarus, part of the north of Ukraine.